Chrystus i Jego dzieło zbawcze w chrzcielnym nauczaniu Ildefonsa z Toledo - Wygralak, Paweł (Vox Patrum, 2019)
The article describes the teaching of Ildefonsus of Toledo on the person of Jesus Christ and his salvific work. The study is based on two writings of the Bishop of Toledo: Do cognitione baptismi and De itinere deserti, in which he conveyed his instruction on the sacrament of baptism. In holy baptism each man, thanks to the passion and resurrection of Christ, receives new life. It can be given to man only by God Himself. Therefore, Ildefonsus emphasizes the truth of the divinty of Jesus Christ, discusses his salvific work and points to the continuing presence of Christ in the life of all the baptized. Jesus Christ grants his prevenient grace to all the baptized, supports them with all the necessary gifts, sets them an example of a life lived in accordance to the will of God the Father. He does all this to lead them to the joy of eternal life. Ildefonsus of Toledo bases his preaching on the Scripture, referring mostly to the texts of the Old Testament and the teaching of St. Paul.